Incremental software architecture : a method for saving failing IT implementations - Bell, Michael, 1957 June 22- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
'This book will depict rare insights into actual failed-to-perform software systems, followed by comprehensive root-cause analyses identifying the reasons for their unsuccessful execution in production. Remedies will be provided that offer strategies to tackle the chief issues. Last, architecture and design best practices will conclude the discussion. The book will assist users to: Mitigate risks of software development projects Increase return on investments (ROI) Provide effective tools to assess technological achievability and viability Introduce software design best practices for enterprise architecture efforts Identify actual software construction value proposition Foster software assets reuse and consolidation Accelerate time-to-market'--
Machine generated contents note: ch. 1 The Need for Incremental Software Architecture -- pt. ONE Why Do Enterprise Systems Fail? -- ch. 2 What Is a Failing Enterprise System? Is It Management's Fault? -- ch. 3 Technological System-Level Failures -- pt. TWO End-State Architecture Discovery and Analysis -- ch. 4 System Fabric Discovery and Analysis -- ch. 5 Application Discovery -- ch. 6 Application Mapping -- pt. THREE End-State Architecture Decomposition -- ch. 7 End-State Architecture Structural Decomposition through Classification -- ch. 8 Business Analysis Drives End-State Architecture Structural Decomposition -- ch. 9 Technical Analysis Drives End-State Architecture Structural Decomposition -- ch. 10 Business Views Drive End-State Architecture Decomposition -- ch. 11 Environment Behavior Drives End-State Architecture Decomposition -- pt. FOUR End-State Architecture Verification -- ch. 12 Design Substantiation -- ch. 13 Introduction to End-State Architecture Stress Testing -- ch. 14 End-State Architecture Stress Testing Driven by Pressure Points -- ch. 15 Enterprise Capacity Planning for End-State Architecture.
Includes index.
Description based on print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Software failures; Evolutionary programming (Computer science); Continuous improvement process; Software architecture; Electronic books